DAKWAH EKONOMI GULEN MOVEMENT: INTEGRASI ISLAM DAN NEOLIBERALISME - Akhmad Rizqon Khamami (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2017)
This article examines the integration of the Gulen Movement into the neoliberal economy. In spite of the Gulen Movement currently undergoes a severe persecution under President Erdogan and charged as FETO (FethullahTerrorist Organization), Gulen’s success story in the economy is of interest for any Islamic movements to emulate. In contrast to those belong to the revivalist Islam that rejects the neo-liberal economy, Gulen does accept the neoliberal economy. He integrates neoliberalism into Islam, and vice versa. Gulenacceptance of the neo-liberal economy, in turn, encouraged his movement to adopt for further neoliberal principles such as human rights, multiculturalism, cosmopolitanism, etc. Since Gulen willingly immerses in the neo-liberalist system, he could be categorized into a progressive Islam. Nevertheless, Galen shows his critical attitude toward the capitalist economy despite his acceptance of the system. This article argues that Gulen’s adoption of the neo-liberal economy is a method of da’wah. This article calls it as ‘da’wah in the economic field’.As it is the case, Gulen’s adoption of neo-liberal economics does not appear simultaneously once, rather through gradual processes in which it goes through three stages of his da’wah: individual transformation, social transformation, and the state.